Critical Discourse Analysis of Political Speech on Human Rights By Prabowo Subiyanto in The First Debate of The 2024 Presidential Election - Khoiron, Khoiron (Journal of Law, Politic and Humanities, 2025)
This study examines how a presidential candidate strategically constructed human rights (HAM) discourse as a political instrument to secure victory in the 2024 Indonesian presidential election. Through the deployment of human rights discourse, Prabowo Subianto sought to influence public perception and voter preferences in his favor. Ultimately, his success in the election demonstrates how political discourse—articulated through public debate texts—effectively shaped public cognition, guided reasoning processes, and influenced electoral choices. The central argument of this article is that human rights discourse, when employed as a political tool, is not ideologically empty. Instead, it functions as a form of political truth production tailored to serve particular interests. The study employs Teun A. van Dijk’s critical discourse analysis (CDA) framework, which integrates three levels of analysis: textual analysis, social cognition, and sociocultural context. What distinguishes this research is its methodological novelty: the application of Van Dijk’s Critical Discourse Analysis (CDA) as a critical intervention in the field of discourse studies, which has often privileged content analysis over a deeper interrogation of textual and discursive structures. Accordingly, this study contributes to the discourse analysis literature by foregrounding the interplay between language, power, and political strategy in the context of contemporary Indonesian electoral politics. The findings of the study reveal three primary discursive strategies: (1) The reframing of human rights as a counter-narrative to legal controversies, (2) The construction of a populist leadership image, and (3) The invocation of “people’s sovereignty” as a protective narrative to legitimize political positioning.